Eriborus argenteopilosus is the most important parasitoid attacking cabbage pest Crocidolomia pavonana in Indonesia. Previous studies proved that parasitoid encapsulation was found to be an important factor limiting the effectiveness of the parasitoid in controlling pest population in the field. Since 1998, we have conducted series studies to investigate encapsulation mechanism developed by hosts against parasitoid, responses of parasitoid toward encapsulation ability and to determine factors t - DAMAYANTI BUCHORI; BANDUNG SAHARI; ENDANG SRI RATNA (HAYATI Journal of Biosciences, 2009)
Eriborus argenteopilosus is the most important parasitoid attacking cabbage pest Crocidolomia pavonana in Indonesia.  Previous studies proved that parasitoid encapsulation was found to be an important factor limiting the effectiveness of the parasitoid in controlling pest population in the field. Since 1998, we have conducted series studies to investigate encapsulation mechanism developed by hosts against parasitoid, responses of parasitoid toward encapsulation ability and to determine factors that may help parasitoid avoid encapsulation. Parasitoid responses were examined on two different hosts C. pavonana and Spodoptera litura. Our findings showed that parasitization level was found to be high both on C. pavonana and S. litura. Encapsulation occurred to be high in all larva stages of C. pavonana, in contrast encapsulation was recorded very low in all larvae stages of S. litura. We recorded that encapsulation in the larval body of C. pavonana was completed in 72 hours and mostly occurred in higher larval stage. Melanization was only recorded in encapsulated parasitoid inside larva body of C. pavonana, not in S. litura. We recorded that encapsulation increased blood cell number of both larvae C. pavonana and S. litura. Encapsulation may affect development of immature parasitoid. Weight of S. litura’s pupae containing encapsulated parasitoid was found to be lower in S. litura, but not in C. pavonana. Our investigation also proved that superparasitism may help parasitoid avoid encapsulation.                   Key words: parasitoid, encapsulation, melanization, blood cell number, superparasitism